The Role of Theology to Identity Politics of Islamic Groups In Indonesia: Study of hadiths Al-Jama'ah in Perspective of Islamic Groups - Muttaqin, Husen Zainal (Jurnal Review Politik, 2017)
The existence of hadith in the Muslim community is very significant. Hadiths that are interpreted in a certain way result to certain religious attitudes and social actions as well. Likewise, with the hadiths on the theme of al-jamaa'ah. Interpretation of the hadiths of al-jamaa'ah implicate to the identity of the group and led to group action which ultimately gave birth to a political identity of groups. This difference in interpretation is theologically influenced by the composition of the revelatory roles, ratios and traditions. There are groups whose tradition’s influence is larger than the others. Great attention to this tradition also differs as in NU which gives large portions to local traditions and salafiyah groups that give large portions to the ancient Arab tradition. There are also more balanced groups between the three components such as PERSIS.